2021
DOI: 10.3390/molecules26237181
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Serum Metabolomics in Rats with Osteoarthritis by Mass Spectrometry

Abstract: Osteoarthritis is a common multifactorial chronic disease that occurs in articular cartilage, subchondral bone, and periarticular tissue. The pathogenesis of OA is still unclear. To investigate the differences in serum metabolites between OA and the control group, liquid chromatography/mass spectrometry (LC/MS)-based metabolomics was used. To reveal the pathogenesis of OA, 12 SD male rats were randomly divided into control and OA groups using collagenase to induce OA for modeling, and serum was collected 7 day… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 40 publications
2
9
0
Order By: Relevance
“…Based on this technology, our study found that the levels of Glutathione (GSH), Ornithine, Aminoadipic acid, Alpha-dimorphecolic acid, Carnosine (CA), and Anserine in KOA rats were return to normal after either T or S treatment. Previous research (35) suggested possible endogenous metabolite biomarkers of the development and progression of KOA, also including Aminoadipic acid, which was partially consistent with our results.…”
Section: Discussionsupporting
confidence: 93%
“…Based on this technology, our study found that the levels of Glutathione (GSH), Ornithine, Aminoadipic acid, Alpha-dimorphecolic acid, Carnosine (CA), and Anserine in KOA rats were return to normal after either T or S treatment. Previous research (35) suggested possible endogenous metabolite biomarkers of the development and progression of KOA, also including Aminoadipic acid, which was partially consistent with our results.…”
Section: Discussionsupporting
confidence: 93%
“…Furthermore, increased abundance of metabolites in the tryptophan metabolic pathway, such as tryptophan, kynurenic acid, and anthranilic acid, have been found in the synovial fluid of patients with rheumatoid arthritis (42). Additionally, increased tryptophan metabolism has been found in the serum of rats with OA and has been suggested as a biomarker for OA (43). In the current study, we also used Seahorse respirometry, and for the first time, discovered that GH promoted long‐chain FAO in chondrocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, NO also alters the function of mitochondria in chondrocytes in OA, which leads to a decrease in cell survival by suppressing the activity of the mitochondrial respiratory chain and ATP synthesis [ 131 ]. The concentration of NO is significantly elevated in the synovial fluid in a model of OA in dogs [ 132 ] and humans [ 133 ]. However, there is evidence that NO has a beneficial effect on some cell types, including osteoblasts.…”
Section: Molecular Mechanisms Of Gasotransmitter-dependent Apoptosis ...mentioning
confidence: 99%